Gerakan Pungut Sampah (GPS) Sebagai Upaya Membangun Kesadaran Lingkungan (Studi Kasus Kelurahan Kampung Baru Kota Sorong - Azalia Fajri Yasin; Nur Abu (CV. Multi Kreasi Media, 2023)
The Litter Picking Movement was carried out after the Workshop activities with the aim of knowing the available information as well as knowledge about solutions in managing polluted environments, especially the ever-present waste problem, and providing understanding especially for future school children, as well as those involved in creating mutual care. Previously, a workshop was held on the role of millennials in creating a clean culture in the environment. Gerakan Pungut Sampah (GPS) is carried out in one of the Tourist Attractions in Sorong City in Kampung Baru Village, a gathering or relaxing place for young people as well as a Crossing Place (Port) to the Sorong Islands District. The results of the first Pungut Sampah Movement (GPS) service, in addition to holding habituation activities (habituation) in changing the culture of the lifestyle of the people in Papua, at the SAR Port of Sorong City managed to collect as many as 114 sacks, with a total weight of 2,124 kg of garbage sacks, including mixed garbage, plastic waste, and glass bottle waste in a day. Second, the habit that is always nurtured will produce care and it will be inherited by children and grandchildren in the future. Third, people's understanding of diverse cultures, religions or gender identities can reduce discrimination and increase tolerance.